2018
DOI: 10.1016/j.athoracsur.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Mediastinal Staging for Lung Cancer by The Society of Thoracic Surgeons Database Participants

Abstract: The STS-GTSD participants performed invasive mediastinal staging more frequently than prior reports, and yet only in a minority of patients. Rates of invasive mediastinal staging vary widely across STS-GTSD participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Our study reinforces the importance of invasive nodal staging, especially as studies suggest that a minority of patients nationwide receive invasive staging with significant center variability. 22,23 Further, in a subgroup analysis of cN3 patients who underwent induction therapy and surgery, we found an 87% pathologic nodal downstaging rate, suggesting that patients with good response to induction therapy were more likely to receive surgery and experience improved survival.…”
Section: Discussionmentioning
confidence: 70%
“…Our study reinforces the importance of invasive nodal staging, especially as studies suggest that a minority of patients nationwide receive invasive staging with significant center variability. 22,23 Further, in a subgroup analysis of cN3 patients who underwent induction therapy and surgery, we found an 87% pathologic nodal downstaging rate, suggesting that patients with good response to induction therapy were more likely to receive surgery and experience improved survival.…”
Section: Discussionmentioning
confidence: 70%
“…Low and variable rates of invasive mediastinal staging form the basis of a perceived gap in the quality of lung cancer care. [1][2][3] A recent prospective study of individuals with suspected or confirmed nonmetastatic lung cancer staged by computed tomography and positron emission tomography showed that 74% had at least one guidelinerecommended indication for invasive mediastinal staging 4 -suggesting that previously reported rates (21%-34%) are lower than they should be. What remains missing is high-level evidence linking process to outcome.…”
mentioning
confidence: 99%
“…7 However, a recent analysis of the Society of Thoracic Surgeons General Thoracic Surgery Database showed that 57% of patients with non-small cell lung cancer clinical stages IB to IIIA did not undergo invasive mediastinal staging. 8 Ignoring the potential evil residing in the mediastinal lymph nodes results in suboptimal outcomes. Therefore, the real hurdle is getting surgeons and patients into the room to have the mediastinum sampled.…”
mentioning
confidence: 99%